Detection of Aspergillus species in blood and bronchoalveolar lavage samples from immunocompromised patients by means of 2-step polymerase chain reaction: Clinical results - Buchheidt, Dieter; Baust, Corinna; Skladny, Heyko; Ritter, Joerg; Suedhoff, Thomas; Baldus, Michael; Seifarth, Wolfgang; Leib-Mösch, Christine; Hehlmann, Rüdiger (Clinical infectious diseases, 2001)
Bronchoalveolar lavage (BAL) samples from 67 patients who were at high risk for invasive aspergillosis were examined using a recently developed 2-step polymerase chain reaction (PCR) that detects <10 fg of Aspergillus DNA in blood and BAL samples in vitro. Thirteen of these patients had PCR and diagnostic results positive for Aspergillus infection. Four patients with possible invasive aspergillosis also had positive PCR results, and the remaining 50 had negative PCR results. In addition, 907 blood samples from 218 high-risk patients were screened. Thirty-three patients with positive PCR results had invasive aspergillosis; 148 patients had PCR and diagnostic results that were negative, and 34 patients with positive PCR results had nonconclusive clinical data. Both blood and BAL testing were performed for 45 patients. All 8 patients with proven invasive aspergillosis showed concordance of positive PCR results. Our data suggest that this PCR method has possible clinical value for confirming and improving the diagnosis of invasive aspergillosis in high-risk patients.